Medición del desgaste ocupacional en trabajadores de farmacias económicas de la ciudad de quevedo - Párraga Hurtado, Lissette Vivianna (2024)
The objective of this study is to assess occupational burnout in employees of Farmacias Económicas in Quevedo, using the Maslach Burnout Inventory (MBI), a validated tool created by Christina Maslach and Susan E. Jackson, which addresses the key dimensions of burnout: emotional exhaustion, depersonalization, and low personal accomplishment. This syndrome, related to psychosocial risks, manifests from repeated exposure to factors causing chronic work-related stress. It has also been linked to workers' ability to handle work demands, their control over tasks, social support, contract types, and work-life balance. The results obtained from the MBI questionnaire highlight that a significant percentage of employees experience emotional exhaustion; 81.25% fall into the medium category of emotional exhaustion, while 18.75% show a high level, with no cases in the low category. The most concerning dimension is depersonalization, evident in 56.25% of employees at high levels. This finding suggests that more than half of the workforce may exhibit signs of coldness and emotional detachment, clear indicators of occupational burnout. Furthermore, 43.75% are at risk of developing the syndrome if not addressed in time. Regarding the personal accomplishment dimension, 37.5% have a low level, indicating a significant proportion of employees with a limited perception of personal accomplishment in their work environment, which is associated with low performance and lack of connection with their work, while 62.5% show a medium level. In general, 25% of the surveyed population, equivalent to 4 workers, display signs of suffering from burnout syndrome, with the possibility that those in medium levels are also at risk of developing it without early intervention. Additionally, a program for preventing and managing occupational burnout is included, taking into account the organizational, social, and personal factors that influence it.